CHARACTER EDUCATION IN THE NATIONAL CURRICULUM: LITERATURE ANALYSIS AND IMPLEMENTATION - Amaludin Bahansubu (International Journal of Teaching and Learning, 2026)
Character education is an important aspect of the national curriculum that aims to shape young people who not only excel academically, but also have strong moral and ethical values. This study analyses various literatures as well as the implementation of character education in schools, identifying the challenges and opportunities that exist. The results of the analysis show that although character education has the support of government policy, its implementation still faces various obstacles such as a lack of understanding and competence of teachers, limited facilities and infrastructure, and a less conducive educational environment. However, opportunities to optimise character education remain large through the use of educational technology, supportive policies, and cooperation with various stakeholders. In conclusion, with commitment and good cooperation, character education can be implemented effectively so as to contribute to the formation of a generation with strong and positive character.